Ibrahim Gafurov's Skill in Creating Historical Characters (Examined through the "GALA" Story) - Sultonova Vazira Nimatovna (Zien Journals, 2024)
This article discusses the interpretation of the image of the great thinker Boborahim Mashrab, as created in the stories by writer Ibrahim G‘afurov. Special attention is given to the expression of Mashrab's personality in the story "Gala"
Keywords: gala; freedom of the heart; philosophic nature; ego